Geophysical Imaging of Permafrost and Talik Configuration Beneath a Thermokarst Lake. (5th January 2017) - You, Yanhui; Yu, Qihao; Pan, Xicai; Wang, Xinbin; Guo, Lei
Abstract: The development of thermokarst lakes in permafrost regions can relate to climate change and significantly impact the hydrological regime. We investigated the configuration of permafrost and a talik under a thermokarst lake on the Qinghai–Tibet Plateau (QTP), China, using GPR, electrical resistivity tomography, drilling and ground temperature measurements. The boundaries and ice content of permafrost and the talik were identified adjacent to and under the lake. The thickness of permafrost differed by about 4 m on opposite sides of the lake. The thickness and extent of ice‐rich permafrost under the northwest shore was greater than under the southeast shore. A talik penetrated the permafrost base beneath both the shallower and deeper parts of the lake, where water depths were all less than the maximum thickness of winter ice. The talik was wider beneath shallower parts of the lake than in deeper areas. This investigation demonstrates that a through‐talik developed although the water depth was less than the maximum thickness of winter ice, indicating that the general relation between water depth and ice thickness is not reliable for identifying the nature of taliks on the QTP. Copyright © 2017 John Wiley & Sons, Ltd.